Nivolumab–ipilimumab in renal cell carcinoma metastatic to the bones: A case report. - Di Napoli, Marilena; Pisano, Carmela; Setola, Sergio Venanzio; Perdonà, Sisto; Feroce, Florinda; Pignata, Sandro (Acta Biomedica Atenei Parmensis, 2022)
In the last recent years, the introduction in the clinical setting of treatment combinations having immune checkpoint inhibitors as the backbone has dramatically improved the outcomes of patients suffering from advanced/metastatic renal cell carcinoma (RCC). Here we report the clinical course of a patient with a rapid and bulky bone recurrence of RCC after nephrectomy, experiencing long-term benefit from nivolumab–ipilimumab administered as first-line treatment.